Training on Basic Gamelan Playing Techniques Based on Tembang Dolanan Creation (Arrangement) at SDN Jombatan 3 Jombang - Wahyudi, Wahyudi; Imron, Ilmawati Fahmi; Nurmilawati, Mumun; Nurwenda, Dhian Dwi; Basori, Moh.; Zunaidah, Farida Nurlaila; Sayuti, Renata Eka; Rianti, Dita Fatma; Rahmawati, Novi Chandra Ayu; Sari, Ayu Titis Rukmana; Sahari, Sutrisno; Hunaifi, Abdul Aziz; Zaman, Wahid Ibnu (CV. Srikandi Kreatif Nusantara in collaboration with Institut Teknologi Mojosari Nganjuk, 2025)
This community service project aims to enhance the understanding and skills of students and teachers at SDN Jombatan 3 Jombang in cultural arts, particularly in playing gamelan musical instruments. The students, representing the Alpha generation, face a lack of knowledge and experience in playing gamelan, leading to a diminished appreciation for local culture. This issue is attributed to the influence of globalization, insufficient Indonesian cultural education, and the perception that gamelan is outdated. To address these challenges, the project introduced gamelan instruments to students to foster a deeper appreciation of Indonesian culture. Methods employed included socialization, training, technology integration, mentoring, and evaluation. The service team conducted needs assessments through observations and interviews, followed by training on basic gamelan techniques using traditional instruments and modern presentation tools. Results indicated an increased enthusiasm for learning gamelan and a better understanding of local cultural arts. Positive feedback from participants highlighted the success of the training. To ensure the sustainability of the program, further training is planned, focusing on creating notation and dolanan songs, which will deepen participants' knowledge and skills in performing arts while preserving local cultural heritage.